Timosaponin-BII inhibits the up-regulation of BACE1 induced by Ferric Chloride in rat retina - Huang Ju-Fang; Shang Lei; Liu Pei; Zhang Meng-Qi; Chen Shuang; Chen Dan; Fan Chun-Ling; Wang Hui; Xiong Kun (BMC Complementary and Alternative Medicine, 2012)
Abstract Background Our previous studies indicated that oxidative stress up-regulated the expression of β-amyloid precursor protein cleavage enzyme-1 (BACE1) in rat retina. Pharmacological reports have shown Timosaponin-BII, a purified extract originating from Chinese medical herb Rhizoma Anemarrhenae, is characterized as an antioxidant. Our present study aimed to determine whether Timosaponin-BII affected the expression of BACE1, β-amyloid precursor protein cleavage production of Aβ1-40 and β-C-terminal fragment (β-CTF) in rat retina, which were pre-treated with the oxidizing agent (solution of FeCl3). Results Few distinctions of BACE1 distribution were observed among all groups (normal control group, model group, Timosaponin-BII treated and vehicle control groups). Rat retinas in model group and vehicle control group manifested an apparent up-regulation of BACE1 expression. Meanwhile, the level of malonaldehyde (MDA), Aβ1-40 and β-CTF were increased. However, when comparing with the vehicle control group, the retinas in Timosaponin-BII treated group showed significantly less BACE1 (p<0.05) and accumulated less Aβ1-40 or β-CTF (p<0.05). It also showed significantly decreased level of MDA (p<0.05) and prolonged partial thromboplastin time (p<0.05). Conclusion Our data suggested that Timosaponin-BII remarkably inhibited the up-regulation of BACE1 and reduced the over-production of β-CTF and Aβ in rat retina, which was induced by FeCl3. The mechanism of Timosaponin-BII on BACE1 expression may be related to its antioxidant property.